Chloride-Induced Corrosion of Steel in Concrete: An Overview on Chloride Diffusion and Prediction of Corrosion Initiation Time. (22nd February 2017) - Khan, Muhammad Umar; Ahmad, Shamsad; Al-Gahtani, Husain Jubran
Abstract : Initiation of corrosion of steel in reinforced concrete (RC) structures subjected to chloride exposures mainly depends on coefficient of chloride diffusion, D c, of concrete. Therefore, D c is one of the key parameters needed for prediction of initiation of reinforcement corrosion. Fick's second law of diffusion has been used for long time to derive the models for chloride diffusion in concrete. However, such models do not include the effects of various significant factors such as chloride binding by the cement, multidirectional ingress of chloride, and variation ofD c with time due to change in the microstructure of concrete during early period of cement hydration. In this paper, a review is presented on the development of chloride diffusion models by incorporating the effects of the key factors into basic Fick's second law of diffusion. Determination of corrosion initiation time using chloride diffusion models is also explained. The information presented in this paper would be useful for accurate prediction of corrosion initiation time of RC structures subjected to chloride exposure, considering the effects of chloride binding, effect of time and space onD c, and interaction effect of multidirectional chloride ingress.